Adenomyosis and it's impact of female infertility - Paniak, Mateusz; Rycąbel, Paweł Maciej; Woszczyńska, Oliwia Brygida; Wojciechowska, Agnieszka Ewelina; Szymura, Marta; Molenda, Marek Jarosław; Wachowska, Maria; Romaniuk, Mateusz; Sowiński, Wojciech Jan; Krawczyk, Michał Brunon (Journal of Education, Health and Sport, 2025)
Introduction: The aim of this review is to explore the relationship between adenomyosis and infertility. The issue of adenomyosis and infertility is the subject of numerous scientific studies due to the mechanisms that may establish a correlation between them. These mechanisms present a dilemma for many researchers, and efforts to address it lead to increasingly innovative solutions for treating infertility and improving the reproductive health of women diagnosed with adenomyosis. Material and methods: We have gathered the available materials and scientific reports, analyzing and summarizing them in a single study. An English-language literature review was conducted. We analysed studies from PubMed up to October 2024 regarding the correlation between adenomyosis and infertility. Aim of study: We aimed to summarize the studies conducted so far by analyzing the available scientific reports to answer the question about adenomyosis correlation in infertility and understand it. Conclusion: The article examines the relationship between adenomyosis and infertility, emphasizing its negative impact on the reproductive potential of women of reproductive age. Adenomyosis reduces pregnancy rates, increases the risk of miscarriages, and hinders embryo implantation, particularly in patients undergoing assisted reproductive techniques. Long protocols with GnRH analogs can improve treatment outcomes in both medical procedures and natural conception attempts. Surgical treatment may enhance fertility but carries risks of complications, and the effectiveness of surgery remains a topic of debate. Accurate diagnosis, appropriate therapy, and improved prenatal care for patients with adenomyosis are essential. Further research, including randomized controlled trials (RCTs), is needed to better understand the impact of adenomyosis on fertility and to develop effective treatment methods.